Reactularization Of Al-Musāwah Principle In Standard Contracts On Murābahah Financing At Bank Syariah - Safwan Safwan; Munawar Rizki Jailani; Nur Sari Dewi.M (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2023)
Murabahah is the sale and purchase of goods at the original price with additional profit agreed between the bank and the customer. The purpose of this research is to examine how the existence of the al-Musawah principle in Murabahah financing at Islamic Banks. The methodology used in this article is qualitative with descriptive analysis. The data were obtained from books related to al-Musawah in Murabahah and interviews with employees and customers of Islamic banks. The results showed that the essence of the principle of al-Musawah is a benchmark for the validity of an agreement, then when viewed in terms of determining the price and period of payment, and risk control in murabahah financing, it is clear that the principle of al-Musawah has not been realized because the contracts are more burdensome for the customer.